Compensation of Health Care Providers in Community Hospitals and Health Centers before and during the Universal Health Care Coverage Scheme of Amnat Charoen Province - มูลสาร, สัมมนา; สินทรัพย์, วุฒิพงษ์ (Journal of Health Science of Thailand, 2021)
The purposes of this study were to determine opinion regarding compensation system and to compare the compensation of health care providers before and during the Universal Health Care Coverage Scheme (June, 2000 - May, 2001 vs. June, 2002 - May, 2003). Subjects were health officials in 5 amphoes of 7 amphoes (except for Amphoes Phana and Mueang) of Amnat Charoen province. Data were collected from financial reports during June, 2000 - May, 2001 and June, 2002 - May, 2003. Moreover, data were also collected by interviewing physicians, dentists, pharmacists, nurses and public health officers, totaling 314. The results showed that before the Universal Health Care Coverage Project health care providers received compensation, on average, less before the scheme (31,679.80 vs. 46,661.56 baht/person/year; respectively). On average, physicians received the highest compensation than one careers even before and during the scheme (14,875 baht per person- month and 34,000 baht person-month, respectively). The lowest compensation was paid to public health officers during both periods (1,695 baht and 2,471 baht per person per month respectively). In addition, the results showed that the health care providers, on average, were satisfied with the compensations paid both before and during the scheme. Most of the health care providers suggested that the District Health Coordinating Committee should manage the compensations in compliance with the Ministry of Public Health Regulation. With limitation, the results of this study can be applied to any other set up.